Nitrogen grain-boundary passivation of In-doped ZnO transparent conducting oxide - FLEISCHER, KARSTEN; SHVETS, IGOR; CAFFREY, DAVID; Ali, D.; Butt, M.Z.; Coughlan, C. (My University, 2018)
We have investigated the properties and conduction limitations of spray pyrolysis grown, low-cost transparent conducting oxide ZnO thin films doped with indium. We analyze the optical, electrical, and crystallographic properties as functions of In content with a specific focus on postgrowth heat treatment of these thin films at 320∘C in an inert, nitrogen atmosphere, which improves the films electrical properties considerably. The effect was found to be dominated by nitrogen-induced grain-boundary passivation, identified by a combined study using in situ resistance measurement upon annealing, x-ray photoelectron spectroscopy, photoluminescence, and x-ray diffraction studies. We also highlight the chemical mechanism of morphologic and crystallographic changes found in films with high indium content. By optimizing growth conditions according to these findings, ZnO:In with a resistivity as low as 2×10−3Ωcm, high optical quality (T≈90%), and sheet resistance of 32Ω/□ has been obtained without any need for postgrowth treatments.
PUBLISHED
Keywords: Adsorption; Composition; Electrical conductivity; Photoemission; Oxides; Chemical vapor deposition; X-ray diffraction; Nanoscience & Materials; Smart & Sustainable Planet; ELECTRICAL CONDUCTIVITY; MOBILITY; Pyrolysis Chemistry; SEMICONDUCTOR DEVICES AND MATERIALS; Transparent Conducting Oxide; XPS; ZNO FILMS